Republic of Belarus : Ex Post Evaluation of Exceptional Access Under the 2009 Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2011)
Belarus was hard hit by the global economic crisis. An exceptional access Stand-By Arrangement (SBA) was, therefore, agreed in early 2009. The program was generally successful and most program conditions were met. The program was overall well designed, but with some shortcomings. While in part owing to external shocks, those problems experienced under the program also reflected rapid directed lending. Lessons from the review are many, the main one is the criticality of incorporating fully ownership, including at the highest levels, in program design and conditionality.